2020
DOI: 10.1002/anie.202006260
|View full text |Cite
|
Sign up to set email alerts
|

Site‐Selective Modification of Peptides and Proteins via Interception of Free‐Radical‐Mediated Dechalcogenation

Abstract: The development of site-selective chemistry targeting the canonical amino acids enables the controlled installation of desired functionalities into native peptides and proteins. Such techniques facilitate the development of polypeptide conjugates to advance therapeutics, diagnostics, and fundamental science. We report a versatile and selective method to functionalize peptides and proteins through free-radical-mediated dechalcogenation. By exploiting phosphine-induced homolysis of the CÀSe and CÀS bonds of sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 65 publications
0
15
0
Order By: Relevance
“…In peptidic systems alanyl-radicals generated in this way have shown promise by taking advantage of phosphine to activate the C β -S γ bond, limited to a peptide scaffold. 27, 28 Such prior strategies for desulfurization at cysteine, cystine or selenenylcysteines proceed via a seemingly complex or likely multiple-manifold process 29 involving the likely intermediate formation of thiophosphoranyl radical adducts as precursors to C• radicals formed upon β-scission. 22, 23 The requirement in these systems for use of phosphines or other P(III) reagents, which are strongly reducing, effectively precludes more general use in typical protein systems since these are commonly used to disrupt disulfides (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…In peptidic systems alanyl-radicals generated in this way have shown promise by taking advantage of phosphine to activate the C β -S γ bond, limited to a peptide scaffold. 27, 28 Such prior strategies for desulfurization at cysteine, cystine or selenenylcysteines proceed via a seemingly complex or likely multiple-manifold process 29 involving the likely intermediate formation of thiophosphoranyl radical adducts as precursors to C• radicals formed upon β-scission. 22, 23 The requirement in these systems for use of phosphines or other P(III) reagents, which are strongly reducing, effectively precludes more general use in typical protein systems since these are commonly used to disrupt disulfides (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Arsenyan’s group reported the use of Cu­(II) to bind and oxidize the Se atom of Ph 2 Se 2 , converting it to the electrophilic PhSe + , which in turn reacted with triple-bond-containing molecules . Almost half a century ago, it was reported that Cu­(II) (and other metal ions) can oxidize phenylhydrazine to generate a phenyl radical, which can react with biomolecules in vivo . ,, Of note, the deselenization reaction of Sec to Ala , (and Ser) , in the presence of TCEP was proposed to go through a radical mechanism, owing to the ability of Se atoms to form radicals under mild conditions . Combining these observations, we envisioned generating radical intermediates from hydrazine reagents with Cu­(II), enabling efficient, chemoselective modification of Sec residues in peptides and proteins (Figure c).…”
Section: Introductionmentioning
confidence: 99%
“…45,53,54 Of note, the deselenization reaction of Sec to Ala 27,28 (and Ser) 28,55 in the presence of TCEP was proposed to go through a radical mechanism, owing to the ability of Se atoms to form radicals under mild conditions. 56 Combining these observations, we envisioned generating radical intermediates from hydrazine reagents with Cu(II), enabling efficient, chemoselective modification of Sec residues in peptides and proteins (Figure 1c).…”
Section: ■ Introductionmentioning
confidence: 99%
“…23,24 The utilization of iridium and ruthenium photocatalysts as thiyl-radical initiators has been extensively studied in desulfurization reactions as well as in a wide variety of bioconjugation techniques. 17,18,[25][26][27][28][29][30] In considering a photophysical process, biocatalytic cofactors, such as derivatives of flavins, possess a higher triplet excited-state energy (E T ∼ 50-65 kcal mol −1 ) than that of typical Ir and Ru catalysts (<50 kcal mol −1 ), [31][32][33] and are currently established as optimized photosensitizers in a series of remarkable bioconjuga- tion or biocompatible reactions as reported by MacMillan [34][35][36] and Glorius 32 (Fig. 1c).…”
mentioning
confidence: 99%